(untitled) (Economic and Political Thought, 2017)
The article aims to analyse China’s international geo-economic strategy that can be described as a dependent variable, i.e. what is explained. To carry out such a research task, two independent variables have been selected: neoliberal institutionalism and China’s cultural and civilizational tradition. This type of research topic solution results from the assumption that China’s international objectives and strategy depends on it own tradition (variables referring to the features of China’s internal system) and the influence of the international system. Taking this into consideration, the author first analyses the content of international geo-economic strategy in the geo-economic space as we;; as measures and methods. He also analyses the content of the assumptions of one of the most important theories of international relations – the neoliberal institutionalism formulated by an American researcher, Robert Keobene, in the 1990s. Another independent variable analysed concerns China’s cultural and civilizational conditions developed in the long history of the country and having contemporary anti-tendencies. The next part of the article refers to the cultural and civilizational issue and discusses the problem of the specificity of China’s economic system. It attempts to answer the question whether this economy meets demanding criteria or is an example of state capitalism. In the author’s opinion, it is a key question and the answer to it is important for China’s own assessment of its economic space.